2021
DOI: 10.1155/2021/2721261
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Image-Guided Moderately Hypofractionated Radiotherapy for Stage III Non-Small-Cell Lung Cancer

Abstract: Objective. To evaluate the efficacy and toxicity of hypofractionated radiotherapy (hypo-RT) for stage III non-small-cell lung cancer (NSCLC) in the Chinese population. Methods. Eighty-six stage III NSCLC patients who received hypo-RT (60 Gy/20 fractions, BED = 78.00 Gy: 73 patients; 62.5 Gy/25 fractions, BED = 78.13 Gy: 13 patients) were recruited. Fifty-seven patients who received conventional radiotherapy (60 Gy/30 fractions, BED = 72.00 Gy) during the same period were enrolled as the control group. All hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Moreover, with the advent of image-guided radiation therapy (IGRT), RT has entered a new era of precision. Our previous studies demonstrated that moderately hypo-RT delivered by IGRT provided a superior prognosis and tolerable toxicity than did conventional RT in Chinese patients with locally advanced NSCLC (5,6). In line with our results, moderately hypo-RT is also being increasingly used to treat unresectable NSCLC worldwide (7,8), particularly in the United Kingdom (9).…”
Section: Introductionsupporting
confidence: 88%
“…Moreover, with the advent of image-guided radiation therapy (IGRT), RT has entered a new era of precision. Our previous studies demonstrated that moderately hypo-RT delivered by IGRT provided a superior prognosis and tolerable toxicity than did conventional RT in Chinese patients with locally advanced NSCLC (5,6). In line with our results, moderately hypo-RT is also being increasingly used to treat unresectable NSCLC worldwide (7,8), particularly in the United Kingdom (9).…”
Section: Introductionsupporting
confidence: 88%
“…1 . Among the 248 studies, 174 studies (85 Asian and 89 non-Asian) with 20,999 patients examined definitive CRT without immunotherapy, 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsmentioning
confidence: 99%
“…Grade 3–4 esophagitis and pneumonitis remained the limiting factor for dose escalation with hypofractionated radiotherapy ( 80 ). However, preliminary results from hypofractionated IGRT for locally advanced NSCLC reported a higher survival and progression-free survival compared to the conventional radiotherapy technique with comparable toxicity most likely due to the higher biologic equivalent dose (BED) ( 81 ). Median survival, local control, and grade 3–4 toxicity were 42 months, 43%, 42.1% and 32 months, 31%, and 47.6% for the hypofractionated group and conventional fractionated group, respectively.…”
Section: Is Cpi Dose Reduction (Rdcpi) An Option For Older Nsclc With...mentioning
confidence: 99%